2008
DOI: 10.1080/1177083x.2008.9522432
|View full text |Cite
|
Sign up to set email alerts
|

Applying the international wellbeing index to investigate subjective wellbeing of New Zealanders with European and with Maori heritage

Abstract: The International Wellbeing Index (IWI), a global measure for investigating subjective wellbeing, consists of a Personal Wellbeing Index (PWI) and a National Wellbeing Index (NWI). The index is applied to the two largest ethnic populations in New Zealand-New Zealanders with European heritage and New Zealanders with Maori heritage. Psychometric characteristics of the IWI for both subsamples compare favourably to those found in other countries. However, for both subsamples, the absolute value of reported subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
3

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…In the New Zealand context, for example, Ganglmair-Wooliscroft and Lawson (2008) reported that the PWI and NWI were internally reliable in representative samples of New Zealand Europeans and Māori, collected in 2005. A Principal Components Analysis reported by Ganglmair-Wooliscroft and Lawson (2008) also indicated that components representing the PWI and NWI were reliably recovered in samples of both New Zealand Europeans, and importantly, also Māori.…”
Section: An Opposing Outcomes Model Of Māori Cultural Efficacymentioning
confidence: 98%
“…In the New Zealand context, for example, Ganglmair-Wooliscroft and Lawson (2008) reported that the PWI and NWI were internally reliable in representative samples of New Zealand Europeans and Māori, collected in 2005. A Principal Components Analysis reported by Ganglmair-Wooliscroft and Lawson (2008) also indicated that components representing the PWI and NWI were reliably recovered in samples of both New Zealand Europeans, and importantly, also Māori.…”
Section: An Opposing Outcomes Model Of Māori Cultural Efficacymentioning
confidence: 98%
“…In their large representative sample collected in 2005 as part of the NZ Consumer Lifestyles Study (NZCLS-05), Ganglmair-Wooliscroft and Lawson (2008) reported that Māori scored lower on both the PWI and NWI. This difference is unsurprising, and we think it likely results from the fact that Māori are disadvantaged relative to NZ Europeans in many domains.…”
Section: Subjective Wellbeing In the New Zealand Contextmentioning
confidence: 98%
“…One was collected in 2005 before the 2007/2010 global financial crisis, and the other in 2009 during the crisis. The 2005 data were drawn from analyses of the NZ Consumer Lifestyles Study (NZCLS-05) as previously reported by Ganglmair-Wooliscroft and Lawson (2008). The 2009 data were drawn from the NZ Attitudes and Values Study (NZAVS-09).…”
mentioning
confidence: 99%
“…Zadovoljstvo se na oba indeksa procjenjuje na skalama od "Uopće nisam zadovoljan" do "Izrazito sam zadovoljan", a rezultat se izražava za svaku dimenziju posebno ili kao prosječni broj bodova za PWI i NWI. Psihometrijske analize pokazuju visoke pokazatelje pouzdanosti (αPWI=0,83-0,85;αNWI=0,85-0,88;Ganglmair-Wooliscroft i Lawson, 2008.;Renn i sur., 2009. ), konvergenciju s drugim mjerama subjektivne dobrobiti te osjetljivost na razlike u spolu, dobi i geografskom položaju, zbog čega se IWI smatra vrijednim instrumentom za obuhvaćanje životno-ga zadovoljstva stanovništva (Cummins i sur., 2003.…”
Section: žIvotno Zadovoljstvounclassified